1996
DOI: 10.1097/00043764-199610000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Overtime Work on 24-Hour Ambulatory Blood Pressure

Abstract: Recently, the adverse effects of long working hours on the cardiovascular systems of workers in Japan, including "Karoshi" (death from overwork), have been the focus of social concern. However, conventional methods of health checkups are often unable to detect the early signs of such adverse effects. To evaluate the influence of overtime work on the cardiovascular system, we compared 24-hour blood pressure measurements among several groups of male white-collar workers. As a result, for those with normal blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
2
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 4 publications
5
118
2
2
Order By: Relevance
“…Two studies had a case-referent design (28,46). There were five independent longitudinal studies (35,36,(38)(39)(40)(41), and two repeatedmeasures studies (30,47). Table 1.…”
Section: Methodological Characteristics and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies had a case-referent design (28,46). There were five independent longitudinal studies (35,36,(38)(39)(40)(41), and two repeatedmeasures studies (30,47). Table 1.…”
Section: Methodological Characteristics and Resultsmentioning
confidence: 99%
“…In within-subject designs, the participants served as their own controls, and confounding of extended hours with psychosocial job characteristics and other factors was less likely to occur. Five studies (30,31,44,45,48) did not control for covariates and reported only univariate between-subject associations. Four studies (26,28,33,38) reported van der Hulst that included a particular outcome measure found an association with long workhours, the direction of the association (+ or -) is given in the last column of the table.…”
Section: Methodological Characteristics and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some work conditions are associated to a risk of developing arterial hypertension independently from age [7,8]. A higher frequency of arterial hypertension has been described in relation to labor factors such as greater antiquity at work [9], time at work -hours in a week (long working hours) [10], psychological stress, and shift work [11].…”
Section: Introductionmentioning
confidence: 99%
“…The association found between prolonged work and risk of acute coronary disease [19,20], could be explained with an excessive activation of the sympathetic nervous system and a rise in arterial pressure levels, together with a reduced activation of the parasympathetic system which in turn, constitutes a risk factor for CHD [21]. After all, arterial hypertension has been associated with work correlated stress [22], a situation that is notoriously associated to an activation of the adrenergic system, to extended work time [23,24] and shift work [3].…”
Section: Introductionmentioning
confidence: 99%